2005
DOI: 10.1021/ci050238c
|View full text |Cite
|
Sign up to set email alerts
|

Screening Drug-Like Compounds by Docking to Homology Models:  A Systematic Study

Abstract: In the absence of an experimentally solved structure, a homology model of a protein target can be used instead for virtual screening of drug candidates by docking and scoring. This approach poses a number of questions regarding the choice of the template to use in constructing the model, the accuracy of the screening results, and the importance of allowing for protein flexibility. The present study addresses such questions with compound screening calculations for multiple homology models of five drug targets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 47 publications
6
93
0
3
Order By: Relevance
“…Indeed several examples in literature, suggest that homology modelling is a viable route to conduct, e.g. screening experiments by high throughput docking [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed several examples in literature, suggest that homology modelling is a viable route to conduct, e.g. screening experiments by high throughput docking [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[27] It is surprising that homology models often provide significant enrichment of actives against a background of decoys. A variety of successful VS studies based [19,[28][29][30] In a retrospective study, Gilson and co-workers [31] analyzed five drug targets for which the crystal structure was available. The VS study showed that some homology models (based on a template with a sequence identity > 30 %) yielded enrichment equal to or even greater than that obtained with the crystal structure of the target.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these databases are made up of molecules that have the properties "drug-like" [98]. Moreover, such models may be used in simulations of "docking" together with the structure of active molecules identified in biological assays.…”
Section: Defensins: Why Exploring Through Theoretical Toolsmentioning
confidence: 99%